Social security as a promising area of administrative law - Калюжний, Ростислав Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
Review of monograph of Bezzubov D. Social Security (organizational and legal principles support) English abstract Successful and systemic reforms of the administration, what is happening today in our country, is impossible without creating a new administrative and legal doctrine that main task is to ensure public safety and the rights of human and legal persons, enforcement of constitutional principles without exception, all spheres of public life and the ultimate rejection of old dogmas of the legal system that focused primarily on satisfying the needs of the state. A notable scientific event on this issue is appearance of the monograph "Social Security: organizational - legal principles of providing", the author – D. Bezzubov.